2020
DOI: 10.22159/ajpcr.2020.v13i7.37717
|View full text |Cite
|
Sign up to set email alerts
|

CORRELATION BETWEEN POLYMORPHISMS OF FOXP3 T-Regulatory PROMOTOR GENE WITH TGF-β IN PATIENTS WITH GRAVES’ DISEASE

Abstract: Objective: The aim of this study is to prove that there are Forkhead Box P3 (FOXP3) T-regulator promoter polymorphisms in Graves’ disease and to analyze the association between FOXP3 T-regulator promoter polymorphisms with transforming growth factor (TGF)-β levels. Methods: This study was an observational study with cross-sectional comparative study design. Consecutive sampling was conducted in patients with Graves’ disease who came to the outpatient clinic and treated in Dr. M. Djamil Hospital, Padang. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In this study, the average levels of TGF-β Graves' disease were found in 1129.21 (323.24) pg/ml, while the research conducted by Elvira et al about the relationship between polymorphism of the T-Regulator FOXP3 gene promoter with TGF-β in Graves' disease patients found that the average levels TGF-β in Graves' disease were higher than in the control group which was 1030.01 (277.64) ng/ml, while the control group was 889.72 (37.86) ng/ml [19]. Kotajima et al (2010) conducted a study on the effect of thyroid hormone and TGF-β on the concentration of cystatin C. This study was conducted in patients with Graves' disease and hypothyroidism who were never given drugs.…”
Section: Discussionmentioning
confidence: 97%
“…In this study, the average levels of TGF-β Graves' disease were found in 1129.21 (323.24) pg/ml, while the research conducted by Elvira et al about the relationship between polymorphism of the T-Regulator FOXP3 gene promoter with TGF-β in Graves' disease patients found that the average levels TGF-β in Graves' disease were higher than in the control group which was 1030.01 (277.64) ng/ml, while the control group was 889.72 (37.86) ng/ml [19]. Kotajima et al (2010) conducted a study on the effect of thyroid hormone and TGF-β on the concentration of cystatin C. This study was conducted in patients with Graves' disease and hypothyroidism who were never given drugs.…”
Section: Discussionmentioning
confidence: 97%